1988
DOI: 10.1111/j.1471-0528.1988.tb06571.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of antihypertensive efficacy and perinatal safety of labetalol and methyldopa in the treatment of hypertension in pregnancy: a randomized controlled trial

Abstract: Summary. Labetalol was compared with methyldopa in a randomized controlled trial involving 176 pregnant women with mild to moderate hypertension. Diastolic blood pressure below 86 mmHg was obtained in a similar proportion of women given labetalol or methyldopa. Intrauterine death occurred in four women treated with methyldopa, and the one neonatal death on day 1 occurred in the labetalol group. The average birthweight and the proportion of preterm or small‐for‐gestational‐age babies were similar in both group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
2
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(34 citation statements)
references
References 16 publications
4
27
2
1
Order By: Relevance
“…4 In Verma et al, study Mean birth weight of Methyldopa group was more than Labetolol group. 5 The Mean birth weight of the present study was also comparable with the studies of Plouin et al, Lamming et al 6,7 Apgar score…”
Section: Discussionsupporting
confidence: 81%
“…4 In Verma et al, study Mean birth weight of Methyldopa group was more than Labetolol group. 5 The Mean birth weight of the present study was also comparable with the studies of Plouin et al, Lamming et al 6,7 Apgar score…”
Section: Discussionsupporting
confidence: 81%
“…This study was also comparable with previous studies Redman et al, Sibai et al, Plouin et al, Pickles et al, Sibai BM et al [6][7][8][9][10] However, few studies say that labetalol provides more efficient control of BP than methyldopa in the treatment of mild hypertension in pregnancy.…”
Section: Discussionsupporting
confidence: 81%
“…There were a total of 3 neonatl deaths, 2 (5%) in methyldopa group and 1 (2.5%) in labetalol group; controversaly, Plouin et al [31] made a findings and our report were not in corroboration with his report. He also demonstrated that four still births in methyldopa group.…”
Section: Discussioncontrasting
confidence: 56%
“…The rest of the patients were multigravidae. However the percentage of primigravidae is greater in most other studies where the prevalence of primigravidae was 50% or above [30,31].…”
Section: Discussionmentioning
confidence: 71%